Query Performance Analysis in NoSQL and Relational Dtabases: MongoDB Vs MySQL - Jose, Benymol; Abraham, Sajimon; Kumar V S, Praveen (International Journal of Computer Sciences and Engineering, 2025)
To improve the data processing of the unstructured data generated, a NoSQL framework can be used to achieve better distribution of storage and analysis work of the collected big data. NoSQL is particularly helpful when a venture needs to get to and investigate huge measure of unstructured information or information that is put away on numerous virtual servers. MongoDB uses an extensive variety of methods to solve the huge information execution issues that ordinary databases were not intended to solve. Relational databases like MySQL are storing data in structured format in tables as rows and columns. This paper concentrates on the advantages of NoSQL databases over relational databases in the analysis of the big data. It mainly uses MongoDB which is one of the boosting technology of NoSQL databases and makes a performance comparison of a particular query in MySQL and MongoDB and justifies why MongoDB is preferred over MySQL